Real Time Power Quality Phenomenon for Various Distribution Feeders - C. Bharatiraja; Harish Chowdary V (Institute of Advanced Engineering and Science, 2016)
Power Quality (PQ) brings more challenges to the large- scale and medium scale industries because in the recent years most of them use high efficiency and low energy devices which cause vulnerable PQ disturbances at Point of Common Coupling (PCC). In this paper, the measurement at different times during load condition and analysis of all types of disturbances occurred has been done. When large rated equipments run, the disturbance (harmonics, RMS variations, and switching transients) levels are very high and poor power factor (PF) has also appeared. Due to this poor PF, reactive power consumption in load increases and accordingly total power increases. An electronic device such as LED lights, fluorescent lamps, computers, copy machines, and laser printers also disturb the supply voltage. We are very well known that every PQ problem directly or indirectly must affect economically. Many researchers have investigated PQ audit for over three decades. However these studies and analysis have been done only at simulation level. Hence, the PQ analyzer based study is required to find out the PQ issues at distribution feeders. It will be a valuable guide for researchers, who are interested in the domain of PQ and wish to explore the opportunities offered by these techniques for further improvement in the field of PQ. This paper gives a brief Real Time PQ measurement using PQ analyzer HIOKI PW3198 at Distribution Feeders and it gives an idea to the researcher to optimize problems-related to PQ with respect to the high rated and low rated electric machinery of different feeders at PCC level. This study further extends to analyze the grid disturbances and looks forward to the optimization methods for each individual PQ disturbance.